2012
DOI: 10.1177/1461445611433787
|View full text |Cite
|
Sign up to set email alerts
|

A search for specificity in understanding CA and context

Abstract: The conversation analytic view of context is often critiqued as being too narrow. In this article, we join the ongoing debate regarding conversation analysis (CA) and context by 1) synthesizing existing scholarly attempts at either conceptualizing or exploring the possibilities of combining CA and ethnography and 2) giving further considerations to whether or how resorting to talk-extrinsic data may be beneficial. We do so by providing four illustrative cases, with increasing complexity, from four different se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Here, in contrast to the study by Waring et al (2012), comments generated in the retrospections have been used in their own right to focus on interactional behaviours and practices that are relevant for language intervention for the children with LI. They have not been used to confirm or disconfirm any observations made through the use of CA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, in contrast to the study by Waring et al (2012), comments generated in the retrospections have been used in their own right to focus on interactional behaviours and practices that are relevant for language intervention for the children with LI. They have not been used to confirm or disconfirm any observations made through the use of CA.…”
Section: Discussionmentioning
confidence: 99%
“…The main point of concern is the relationship between what practices can be demonstrably observed, and participants' retrospective, video-stimulated comments. Waring et al (2012) suggested that talk-extrinsic data may confirm CA observations, specify assumptions of why something takes place in interaction, disambiguate an earlier analysis, and correct an initial analysis. In response to this claim, Antaki (2012), Ford (2012) and Pomerantz (2012) stress that it is important not to make straightforward assumptions of peoples' underlying intentions for their interactional practises only based on their self-reports (Ford, 2012), as these are in themselves (re)constructions of a past event.…”
Section: Conversation Analysis In Combination With Talk-extrinsic Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Combining CA with other approaches in a single study may present certain tensions arising from the incompatibility of the epistemological assumptions underlying each approach (although see Waring et al., ; Waring & Hruska, ). However, my ultimate analytical goal was to establish how the understanding gleaned from the multiple approaches could contribute to constructing the ecology of language learning in the classroom (van Lier, ) and inform the kind of teacher education interventions needed to help teachers harness opportunities for students’ language learning available in TLD.…”
mentioning
confidence: 99%
“…In particular, in our analysis we selectively draw on the information about participants' backgrounds that was obtained in the interviews with the participants prior to and after the consultations. Such an approach of combining the analysis of interactional data with ethnographic observations yields additional insights into the analyzed interactions (for the advantages of this method see Maynard 2003;Silverman 1999;Pomerantz 2005;Waring 2012). The approach also proves particularly useful in analyzing such complex phenomenon as laughter in all its instantiations so as to shed light on its various conversational functions, including both 'playful' and 'serious' ones.…”
Section: Methodsmentioning
confidence: 99%